Effectiveness of Provisioning Local Microorganisms Bamboo Shoots (Dendrocalamus Asper) on The Quality of Compost From Sugarcane Waste (Baggase) - Sofi Karina Fridayanti; Marlik; Imam Thohari; Nur Haidah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2023)
Garbage is still a severe problem for poor and developing countries. Population growth, as well as changes in public consumption, are the causes of the continued amount of waste. Efforts must be made to prevent the emergence of bagasse waste in the sugar industry and the community. Prevention can be done by utilizing bagasse waste as organic material in compost that is beneficial for plant growth with the addition of local microorganisms (MOL). Research with pure experiment posttest Only Control Group. This study aims to determine the effect of bamboo shoots' local microorganisms (MOL) on compost quality from bagasse waste. The number of samples was 10 with 3 times replication and 1 control. The sampling technique was done by random sampling. The C/N Ratio for giving MOL 50 ml was 22.9, the C/N Ratio for giving MOL 100 ml was 22.5, the C/N ratio for giving MOL 150 ml was 20.2, and the C/N ratio for giving MOL was 25.9. There is an effect of giving a lot of MOL to the resulting C/N ratio (p = 0.005). The community needs to add innovations by processing bagasse waste into compost that can be used to reduce the amount of waste generation and apply it to plants.